Thermophysical calculations the process sedimentation beeswax - Struchaiev, Mykola; Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Postol, Yuliia; Постол, Юлія Олександрівна; Постол, Юлия Александровна; Popriadukhin, Vadym; Попрядухін, Вадим Сергійович; Попрядухин, Вадим Сергеевич; Borokhov, Ivan; Борохов, Іван Валерійович; Борохов, Иван Валерьевич; et al. (ТДАТУ, 2020)
EN: The article is devoted to improving the efficiency of cleaning wax from contaminants by reducing heat energy losses, the rate of temperature reduction; a method for the thermal calculation of compact heat-insulated tank is proposed on the example of reducing energy losses during the deposition of contaminants from wax in a molten state. Primary wax contains many polluting components, such as bee bread, merva, more than 15 different organic compounds and scrapings of frames and so on. The most common method of wax cleaning is its long settling in the molten form, followed by crystallization and removal (cutting) of the settled layer of contaminants. The aim of the study is to establish the possibility of improving the energy efficiency of the deposition of contaminants from wax in a molten state by reducing energy consumption to maintain its temperature, installing heat insulation, determining the optimal location and calculation of the boiler to compensate for heat losses. To create rational temperature conditions under which it is possible to clean the wax from contaminants, it is necessary to take into account the thermophysical properties of the wax, as well as data on its basic physical and mechanical properties. The calculation of the amount of heat for the deposition of contaminants from the wax, which is in the molten state, in a tank of complex shape is performed on the basis of a joint solution of the heat balance and heat transfer equation. The amount of heat required for heating water, wax, steel tank and heat insulation, melting and overheating of wax is determined. The layout of the elements of the installation for cleaning wax is proposed. The heat losses of all sections of a thermally insulated tank of complex shape for the deposition of contaminants from wax, insulated with basalt wool mats were determined. The surface temperatures of the outer layer of thermal insulation are determined for different arrangement of elements. The proposed methodology for calculating heat loss can be used in the design of thermal insulation of complex containers for the deposition of contaminants from wax. RU: Статья посвящена повышению эффективности очистки воска от загрязнений, путем снижения потерь тепловой энергии, темпа снижения температуры, предложена методика теплового расчета компактных теплоизолированных ёмкостей на примере уменьшения потерь энергии в процессе осаждения загрязнений из воска, находящегося в расплавленном состоянии. Воск первичной перетопки содержит множество загрязняющих его компонентов, таких как перга, мерва, более 15 различных органических соединений, соскобы рамок и так далее. Наиболее распространенным методом очистки воска является его длительное отстаивание в расплавленном виде с последующей кристаллизацией и удалением (срезанием) осевшего слоя загрязнений. Целью исследования является установление возможности повышения энергоэффективности осаждения загрязнений из воска, находящегося в расплавленном состоянии путем снижения энергозатрат на поддержание его температуры, установкой теплоизоляции, определения оптимального расположения и расчета котла для компенсации тепловых потерь. UK: Стаття присвячена підвищенню ефективності очищення воску від забруднень, шляхом зниження втрат теплової енергії, темпу зниження температури, запропонована методика теплового розрахунку компактних теплоізольованих ємностей на прикладі зменшення втрат енергії в процесі осадження забруднень з воску, що знаходиться в розплавленому стані. Віск первинної перетоплювання містить безліч забруднюючих його компонентів, таких як перга, мерва, більше 15 різних органічних сполук, зіскрібки рамок і так далі. Найбільш поширеним методом очищення воску є його тривале відстоювання в розплавленому вигляді з подальшою кристалізацією і видаленням (зрізанням) шару забруднень. Метою дослідження є встановлення можливості підвищення енергоефективності осадження забруднень з воску, що знаходиться в розплавленому стані шляхом зниження енерговитрат на підтримку його температури, установкою теплоізоляції, визначення оптимального розташування та розрахунку котла для компенсації теплових втрат.
Теплофізичниі розрахунки процесу седиментації бджолиного воску
Теплофизические расчеты процесса седиментации пчелиного воска
Keywords: energy saving; thermal insulation; energy loss; compact containers of complex shape,; deposition, pollution; wax cleaning; сохранение энергии; потеря энергии; загрязнение; теплоизоляция; чистка воском; очищення воском; енергозбереження; втрати енергії; забруднення; термоізоляція